2011
DOI: 10.1143/apex.5.012301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu$_{2}$ZnSn(S,Se)$_{4}$ Nanoparticles for Application in Low-Cost Solar Cells

Abstract: A low-temperature colloid synthesis approach was applied to synthesize Cu2ZnSn(S,Se)4 (CZTSSe) nanoparticles for the first time. This method produced gram quantities of material with a chemical yield in excess of 90% within a short synthesis time. Average sizes of 80 nm nanoparticles with narrow diameter distribution were achieved using Na2S with Na2Se as a chalcogenide source. The formation reaction of kesterite CZTSSe fabricated from synthesized nanoparticles was investigated, and the results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 16 publications
1
21
1
Order By: Relevance
“…19) using a colloidal dispersion of Cu-Zn-Sn-S-Se in pyridine and methanol, coated with an ultrasonic spray, and annealed in an atmosphere containing H 2 as well as Se and Sn vapours. The authors commented that they could not achieve good lm morphologies by spraying the colloids containing only sulphur, 20 and that they had to use a mixture of sulphur and selenium to achieve functional devices.…”
Section: Introductionmentioning
confidence: 99%
“…19) using a colloidal dispersion of Cu-Zn-Sn-S-Se in pyridine and methanol, coated with an ultrasonic spray, and annealed in an atmosphere containing H 2 as well as Se and Sn vapours. The authors commented that they could not achieve good lm morphologies by spraying the colloids containing only sulphur, 20 and that they had to use a mixture of sulphur and selenium to achieve functional devices.…”
Section: Introductionmentioning
confidence: 99%
“…Film Fabrication : Cu‐poor, Zn‐rich Cu 2 ZnSnSe 4 (CZTSe) nanoparticles were prepared according to the method reported in Ref . In the typical synthesis, CuI (2.79 mmol), ZnI 2 (1.68 mmol), and SnI 4 (1.60 mmol) were added to 500 ml of pyridine as a metal source and then cooled to 0 °C by stirring until a clear solution was obtained.…”
Section: Methodsmentioning
confidence: 99%
“…11, were used as the starting materials. In the typical synthesis, CuI (2.88 mmol), ZnI 2 (1.76 mmol), and SnI 4 (1.60 mmol) were added to pyridine as a metal source and then cooled to 0°C by stirring until a clear solution was obtained.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…By using CZTSSe nanoparticles, Guo et al reported a 7.2% solar cell, Cao et al prepared an 8.4% solar cell, and Zhang et al fabricated a 5.4% solar cell. [9][10][11] To date, despite the fact that the nanoparticle coating technique has attracted much attention, the efficiency of the CZTSSe solar cells fabricated by this approach is still lower than that of the cells prepared by hydrazine-based approaches.…”
Section: Introductionmentioning
confidence: 99%